2015
DOI: 10.15740/has/ijas/11.1/54-58
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake, yield and protein content of chickpea (Cicer arietinum L.) as influenced by irrigation and sulphur levels in medium black soils

Abstract: : A field experiment was carried out at Junagadh Agricultural University, Junagadh, Gujarat during Rabi 2010-11 to study the nutrient uptake, yield and quality of chickpea as influenced by irrigation and sulphur levels. Irrigation and sulphur have shown significant influence on growth, yield, nutrient uptake and protein content of chickpea. Among four irrigation schedules, irrigation scheduled at 0.9 IW/CPE ratio recorded significantly higher values for nutrient uptake, grain and stover yield, protein content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
6
2
0
Order By: Relevance
“…The lowest Grain yield of chickpea (1488 Kg ha -1 ) was recorded in absolute control. Our results are in line with Srinivasulu et al [11], reported the effect of sulphur application in increasing the Grain and straw yield of chickpea, while Das et al [4], reported increase in growth, plant yield and yield attributing characters of chickpea with increasing sulphur doses. The increasing in yield might be due to the fact that S perform many physiological functions in Cysteine, methionine and chlorophyll Synthesis.Thus these bioactivities of sulphur might have played important role in improving yield attributing characters and yield of chickpea.…”
Section: Yield Of Chickpeasupporting
confidence: 92%
See 1 more Smart Citation
“…The lowest Grain yield of chickpea (1488 Kg ha -1 ) was recorded in absolute control. Our results are in line with Srinivasulu et al [11], reported the effect of sulphur application in increasing the Grain and straw yield of chickpea, while Das et al [4], reported increase in growth, plant yield and yield attributing characters of chickpea with increasing sulphur doses. The increasing in yield might be due to the fact that S perform many physiological functions in Cysteine, methionine and chlorophyll Synthesis.Thus these bioactivities of sulphur might have played important role in improving yield attributing characters and yield of chickpea.…”
Section: Yield Of Chickpeasupporting
confidence: 92%
“…Jadeja et al [15], also reported increased Grain and straw yield of chickpea with sulphur application as compared to control. Similar finding of increased stover yield with sulphur application were also given by Srinivasulu et al [11] Fayaz et al [13] and Bhuriya et al [14].…”
Section: Yield Of Chickpeasupporting
confidence: 85%
“…Zn is involved in auxin metabolism like, tryptophane synthesis, tryptamine metabolism, protein synthesis, formation of nucleic acid and helps in utilization of nitrogen as well as phosphorus by plants (Ram and Katiyar, 2013). Similar to the current findings N uptake increase due to rhizobium inoculation, S and Zn application have been reported by several literatures (Abdalla et al, 2011;Das et al, 2016;Desta et al, 2015;El-kade and Mona, 2013;Hussain et al, 2011;Islam et al, 2013;Jay et al, 2012;Kesare, 2014;Mondal et al, 2005;Najar et al, 2011;Rokhzadi and Toashih, 2011;Shamima and Farid, 2006;Srinivasulu et al, 2015;Srivastava et al, 2006;Togay et al, 2008;Zaidi et al, 2003;Zerihun et al, 2017) Total phosphorus uptake…”
Section: Total Nitrogen Uptakesupporting
confidence: 91%
“…The sulphur plays an important role in synthesis of S containing amino acids, namely methionine, cysteine and cystine resulted in increased in protein content in chickpea. Similar results were observed by Patel et al (2014) [13] , Srinivasulu et al (2015) [17] and Yadav et al (2020) [18] .…”
Section: Effect Of Sulphursupporting
confidence: 89%